PENGARUH LEVERAGE, LIKUIDITAS, PERTUMBUHAN PERUSAHAAN, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Rendy Rendy; Tony Sudirgo (Jurnal Paradigma Akuntansi, 2023)
The purpose of this research is to analyze the effect of leverage, liquidity, firm growth, and firm size on firm value in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2020 period. The research here uses a purposive sampling method with a sample consisting of 68 manufacturing companies, and processing is carried out usingEviews 12 program. This research shows that leverage has a significant positive effect on firm value, liquidity does not have a significant negative effect on firm value, while firm growth and firm size do not have a significant positive effect on firm value.